2020
DOI: 10.1177/0271678x19899377
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of spontaneous microhemorrhage formation in mice with cerebral amyloid angiopathy

Abstract: The pathophysiology of microhemorrhages in the context of cerebral amyloid angiopathy (CAA) remains poorly understood. Here we used in vivo two-photon microscopy in aged APP/PS1 mice with mild-to-moderate CAA to assess the formation of microhemorrhages and their spatial relationship with vascular Aβ depositions in the surrounding microvascular network. Mice with chronic cranial windows were intravenously injected with fluorescent dextran to visualize the vessels and a fluorescently labeled anti-fibrin antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…As such, it seems plausible that the altered flow field is a possible mechanism by which to affect Aβ deposition and clearance [17] or solute clearance via the perivascular space in general [35]. The local disturbances in the flow field and in solute clearance could build-up and cause additional vessel ruptures [6] or occlusions, which subsequently might further impede clearance [37,57] as well as oxygen and nutrient supply in an increasing area around the MSC. It is important to note that currently the key mechanisms causing the differences in Aβ deposition in response to capillary occlusion are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, it seems plausible that the altered flow field is a possible mechanism by which to affect Aβ deposition and clearance [17] or solute clearance via the perivascular space in general [35]. The local disturbances in the flow field and in solute clearance could build-up and cause additional vessel ruptures [6] or occlusions, which subsequently might further impede clearance [37,57] as well as oxygen and nutrient supply in an increasing area around the MSC. It is important to note that currently the key mechanisms causing the differences in Aβ deposition in response to capillary occlusion are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades it has become evident that microinfarcts are linked to various pathologies, e.g. cerebral amyloid angiopathy (CAA), cognitive impairment, Alzheimer's disease (AD) and dementia [6][7][8][9][10]. For example, postmortem neuropathological studies revealed that 62% of patients with vascular dementia also suffered from cortical microinfarcts [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008 ; van Veluw et al. 2016 ) has been recently probed in APP/PS1 mice with CAA ( van Veluw et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…2020 ). Although the presence of vascular Aβ deposits in these mice did not directly predispose arterioles in their brains to leak, the physical alterations surrounding the vascular network likely contributed to the formation of spontaneous leakage sites ( van Veluw et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%